Semarang City's Resilient Strategy Facing Covid-19 - Adi Ekopriyono (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2021)
Semarang City is the first city in Indonesia to be selected in the 100Resilient Cities (100 RC) Program. This position raises the hope that thiscity has more potential than other cities to prevent and control the spread ofCovid-19. The policies pursued through Restrictions on CommunityActivities and the Candi Hebat Siaga Village Program have not yet beenoptimal in breaking the chain of Covid-19 spread. This study uses adescriptive qualitative approach, examines the factors that influence, andformulates the steps that need to be taken to increase its effectiveness. Themost prominent factor found in this study is the weak resilience of localculture concerning the prevention and control of Covid-19. This weaknesscauses the community to be less disciplined in implementing health protocolsand the apparatus less control over the implementation of policies.